Efektivitas Media Real Time Augmented Reality Bubut pada Mata Kuliah Teknologi Pemesinan Program Studi D III Departemen Teknik Mesin FT-UNP - Muhammad Iqbal Parezi; Primawati Primawati; Febri Prasetya (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Learning activities can run smoothly if accompanied by the availability of appropriate learning media. Learning in the Machining Technology course requires direct practical activities, for example in understanding the use of lathes. The limitations of students' mastery of knowledge when facing the teaching and learning process that tends to be lecture-oriented, causing students' lack of understanding during practice. Learning media that is less interesting causes failure in delivering material, thereby reducing students' interest in learning. This study aims to examine the effectiveness of Real Time Augmented Reality (RT-AR) Lathe media in the learning process of the Machining Technology course in the D-III Study Program, Department of Mechanical Engineering, Faculty of Engineering, Padang State University (FT-UNP). RT-AR media is designed to present interactive visualizations that describe the lathe work process in real time, so that it is expected to improve students' conceptual understanding and practical skills. The study used a quasi-experimental method with a pre-test and post-test design in two groups: the experimental group using RT-AR media and the control group using conventional learning methods. The results showed that there was a significant increase in the learning outcomes of students in the experimental group compared to the control group. In addition, RT-AR media is also able to increase students' motivation and active participation during the learning process. These findings indicate that RT-AR Lathe media is an effective and relevant learning innovation to be applied in vocational engineering education, especially in mastering lathing material.